(untitled) (Strathmore Law Review, 2023)
The right to strike of medical practitioners under the Constitution of Kenya (2010), is the best tool that an employee has against non-performance by an employer, given that both parties have varying bargaining powers. There exists an endemic nexus between the right to healthcare services guaranteed by the Constitution of Kenya, the right to health as well as the right to strike for healthcare practitioners. This delicate relationship between these competing rights necessitates a harmonious balance between them that will achieve the greatest good. This article analyses the concept of essential services and the rights and limitations of those rights that medical practitioners have as essential service providers. It looks at how the Kenyan courts as well as different jurisdictions have handled the issue altogether, in an attempt to strike a balance between the two conflicting rights. While striking a balance between these two competing rights, the path that will lead to serving the best interest of the public, both in personam and in rem has to be taken not only by the courts and legislature but other relevant stakeholders including the medical practitioners and their employers. The steps taken thus far by the Employment and Labour Relations Court (ELRC) in adopting the concept of minimal service during strikes by medical practitioners, who are essential service providers, are notable but a lot is left to be desired to achieve legal certainty.